2010
DOI: 10.1111/j.1600-0625.2009.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of IL‐18 and sIL‐2R in patients with alopecia areata receiving combined therapy with oral cyclosporine and steroids

Abstract: This study was to determine which immunologic factors contribute to the prognosis of patients with alopecia areata (AA) who were receiving oral cyclosporine A and methylprednisolone. Patients with >25% hair regrowth were defined as responders, and patients exhibiting £25% regrowth were poor-responders. The serum levels of IL-18 and soluble IL-2 receptor (sIL-2R) were measured at baseline in 21 patients with AA and 22 control subjects. The mean serum level of IL-18 in the patients with extensive AA was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…It is also possible that AA activated lymphocytes release IL18 into circulation as observed in other autoimmune diseases [80]. Increased IL18 has been found in AA patient plasma [81]. Increased IL18 activity in the heart could lead to cardiac hypertrophy and increased cell apoptosis without direct lymphocyte infiltration [65].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that AA activated lymphocytes release IL18 into circulation as observed in other autoimmune diseases [80]. Increased IL18 has been found in AA patient plasma [81]. Increased IL18 activity in the heart could lead to cardiac hypertrophy and increased cell apoptosis without direct lymphocyte infiltration [65].…”
Section: Discussionmentioning
confidence: 99%
“…The combined therapeutic effect of cyclosporin and systemic steroids has been studied extensively. The efficacy rates of this combination vary widely (25–76.7%) . Still, few robust studies of cyclosporin as a monotherapy have been conducted.…”
Section: Third‐line Therapiesmentioning
confidence: 99%
“…A recent study showed that a good response to oral cyclosporine can be predicted if the serum level of IL 18 is elevated and the level of soluble IL 2 receptor is low 61. The use of oral cyclosporine in patients with alopecia areata is not generally favored due to its adverse event profile (nephrotoxicity, immune suppression, and hypertension) and a high relapse rate (up to 100%) 62.…”
Section: Third-line Therapiesmentioning
confidence: 99%